Structure
By adjusting the physical characteristics of the first film and the second film, such as the pant-shaped tear force and haze, and color differences, the problem of difficult film distinction in the printed circuit board and large deviation from the resin layer thickness is solved, thereby achieving efficient sealing of the resin layer and improving the film strength.
Patent Information
- Application Number
- CN202180015814.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-31
- Filing Date
- 2021-03-24
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-03-24
AI Technical Summary
In the printed circuit board manufactured by the layering method, the first film and the second film are difficult to distinguish, resulting in film traces easily occurring in the resin layer when the second film is peeled off, and when the resin layer having a thickness of 50 μm or more is formed, the thickness deviation of the resin layer is large.
By adjusting the difference in the trouser tearing force and haze between the first and second films, the difference in the L*, a*, and b* values in the Lab color space can reach more than a certain extent, so that it is easy to distinguish the inside and outside of the structure and inhibit the occurrence of film traces. At the same time, the thickness of the first film and the tear force in the pant-shaped are adjusted to ensure that the thickness deviation of the resin layer is small.
It is realized that the resin layer does not easily have film marks when peeling off the second film, and a resin layer with a thickness of 50 μm or more and a thickness deviation is formed on the first film, thereby improving the distinction and sealing properties of the structure.
Smart Images

Figure CN115135496B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a structure, and more specifically, to a structure including a first film and a resin layer, or a structure including a first film, a resin layer, and a second film in this order. Background Art
[0002] As a method for manufacturing a printed circuit board, a method for manufacturing a printed circuit board based on a build-up method in which an insulating layer and a conductive layer are alternately stacked is widely used. In a manufacturing method based on the build-up method, the insulating layer is generally formed by thermally curing a curable resin composition as a curable resin layer.
[0003] In recent years, it has been proposed to form the insulating layer used in the above-mentioned manufacturing method based on the build-up method by a dry film type. The dry film is a structure having a curable resin layer obtained by applying a liquid curable resin composition adjusted to a predetermined viscosity to a region on the surface of a separately prepared first film and then drying it. In addition, the dry film is usually further laminated with a second film to protect the surface of the curable resin layer on the opposite side of the first film.
[0004] For the above-mentioned structure, the process has a sequence in which the first film is peeled off after the second film is peeled off, after lamination with the substrate or after curing, so a method is required to distinguish which film of the first film and the second film is peeled off. However, in the above-mentioned structure, when both the first film and the second film are transparent, it is difficult to distinguish the films, and there is a possibility of mistaking the order of peeling the first film and the second film. In particular, if the first film and the second film use films of the same specification, this tendency is significant, and in this case, when the second film is peeled off from the structure, there is also the problem of linear marks (hereinafter referred to as "film marks") generated in the resin layer due to the relationship with the first film. Therefore, as a method for easily distinguishing the inside and outside of the structure, for example, a coloring layer is provided on one surface so that the color difference between the inside and outside can be visually identified (see patent document 1).
[0005] In addition, in the past, the sealing of chip-type devices (chip components) such as semiconductor elements and electronic components was carried out by transfer molding using a powdered epoxy resin composition, potting using a liquid epoxy resin composition or a silicone resin, dispensing, printing, etc. However, at present, in order to be suitable for being mounted on highly integrated devices and efficiently manufacturing surface acoustic wave (SAW) devices or crystal devices, which need to be hollow inside after sealing, it is necessary to seal and package them together on a substrate having multiple chip-type devices.
[0006] For example, Patent Document 2 proposes a thermosetting resin composition as a composition capable of collective sealing, characterized in that it comprises (A) a crosslinkable elastomer, (B) an epoxy resin, (C) an epoxy resin curing agent, and (D) an inorganic filler. In addition, collective sealing by a dry film type has also been proposed in recent years.
[0007] The dry film is generally a structure having a curable resin layer on a first film. Generally, the above structure can be produced by coating a liquid curable resin composition on a first film to which tension is applied and then drying the composition to form a curable resin layer.
[0008] Incidentally, the first film for the structure is used by unwinding the film wound on the roll, but there is a problem of wrinkling or loosening of the film at this time. In response to such a problem, the following scheme is proposed: the roll circumference D1 to D14 of each part when the film roll is divided into 14 equal parts in the width direction satisfies a specific condition, and the maximum thickness difference (Tm) of the film thickness T1 to T14 of each part measured straightly in the width direction of the 14-divided film roll satisfies a specific condition (see Patent Document 3).
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2010-069760
[0012] Patent Document 2: Japanese Patent Application Publication No. 2015-166403
[0013] Patent Document 3: Japanese Patent Application Publication No. 2016-44035 Summary of the invention
[0014] Problems to be solved by the invention
[0015] <Issues of the First Method>
[0016] However, in the method of Patent Document 1, since the colored layer is provided as a layer different from the thermoplastic films bonded to both surfaces of the core material, there is a problem that the number of steps increases and the production cost increases.
[0017] Therefore, an object of a first aspect of the present invention is to provide a structure in which a first film and a second film of a multilayer structure are easily distinguished and a resin layer is less likely to have film marks when the second film is peeled off.
[0018] <Issues of the Second Method>
[0019] In addition, in the structures such as Patent Documents 2 and 3, the following problem was found: when the first film is thin, longitudinal wrinkles will be generated when tension is applied to the first film. On the other hand, when the thickness of the resin layer is thin, even if the first film is wrinkled, a resin layer with a small thickness deviation can be formed following the wrinkles. However, when the thickness of the resin layer is thick, for example, 50 μm or more, when the resin layer is formed on the first film, the liquid curable resin composition applied to the wrinkle valley of the first film accumulates, and as a result, a problem of forming a resin layer with a large thickness deviation after drying was found.
[0020] Therefore, an object of a second aspect of the present invention is to provide a structure including a resin layer having a thickness of 50 μm or more and a small variation in thickness on a first film.
[0021] Means for solving problems
[0022] <Method of the first method>
[0023] The inventors of the present invention have conducted in-depth research to achieve the purpose of the above-mentioned first method, and found that by adjusting the haze of the first film and the second film themselves, or the L* value, a* value, b* value in the Lab color space measured from the first film side of the structure and the L* value, a* value, b* value in the Lab color space measured from the second film side of the structure, a certain difference or more is given to each haze or each L* value, a* value or b* value, thereby making it easy to distinguish the inside and outside of the structure.
[0024] The present inventors have conducted intensive studies to solve the above problems and have found that the occurrence of film marks can be suppressed by adjusting the trouser tear strengths of the first film and the second film and providing a certain or greater difference in the trouser tear strengths.
[0025] That is, the structure of the first aspect for the purpose of the first aspect of the present invention is characterized in that it includes a first film, a resin layer, and a second film in this order,
[0026] The difference between the trouser-shaped tearing force of the first film and the trouser-shaped tearing force of the second film is -0.05N or less or +0.05N or more,
[0027] The difference in haze between the first film and the second film is -5% or less or +5% or more.
[0028] A second aspect of the structure for the purpose of the first aspect of the present invention is characterized in that it includes a first film, a resin layer, and a second film in this order,
[0029] The difference between the trouser-shaped tearing force of the first film and the trouser-shaped tearing force of the second film is -0.05N or less or +0.05N or more,
[0030] The difference between the L* value, a* value, and b* value in the Lab color space measured from the first film side of the structure and the L* value, a* value, and b* value in the Lab color space measured from the second film side of the structure satisfies at least one of the following conditions (i) to (iii),
[0031] (i) The difference in L* value is less than -0.1 or greater than +0.1;
[0032] (ii) the difference in a* values is less than -0.1 or greater than +0.1;
[0033] (iii) The difference in b* value is -1 or less or +1 or more.
[0034] In the first and second aspects for the purpose of the first aspect of the present invention, it is preferred that the trouser tear strength of the second film is smaller than the trouser tear strength of the first film.
[0035] In the first and second aspects for the purpose of the first aspect of the present invention, the resin layer is preferably a curable resin layer.
[0036] In the first and second aspects for the purpose of the first aspect of the present invention, the first film is preferably selected from polyester films and polyolefin films.
[0037] In the first and second aspects for the purpose of the first aspect of the present invention, the second film is preferably selected from polyester films and polyolefin films.
[0038] <Method of the Second Method>
[0039] The inventors of the present invention have conducted intensive research to achieve the purpose of the second embodiment, and have found that when forming a resin layer having a thickness of 50 μm or more, by adjusting the trouser tear force of the first film and adjusting the thickness of the first film, a resin layer having a small thickness deviation can be formed. The present invention is based on the above technical idea.
[0040] The structure of the embodiment of the present invention is characterized by comprising a first film and a resin layer.
[0041] The thickness of the first film is 30 μm or more.
[0042] The trouser-shaped tearing force of the first film is greater than 0.1N.
[0043] The thickness of the resin layer is 50 μm or more.
[0044] The resin layer is a curable resin layer.
[0045] In the embodiment for achieving the object of the second aspect of the present invention, the curable resin layer preferably contains a thermosetting resin and a curing agent.
[0046] In an embodiment related to the object of the second aspect of the present invention, the thermosetting resin is preferably an epoxy compound.
[0047] In the embodiment for achieving the object of the second aspect of the present invention, the resin layer is preferably a curable resin layer.
[0048] In an embodiment directed to the object of the second aspect of the present invention, the first film is preferably selected from the group consisting of polyester films, polyolefin films, and polyimide films.
[0049] In an aspect aimed at the object of the second aspect of the present invention, it is preferable that the variation in thickness of the first film is ±10% or less.
[0050] Effects of the Invention
[0051] <Effect of the First Method>
[0052] According to the present invention, a structure can be provided in which the front and back sides of the multilayer structure can be easily distinguished and the resin layer is less likely to have film marks when the second film is peeled off.
[0053] The reason why the trouser-shaped tearing force of the first film and the second film is adjusted and a certain difference is given to each trouser-shaped tearing force, thereby suppressing the generation of film marks is not necessarily clear, but it can be inferred as follows. That is, if a difference in trouser-shaped tearing force is given, the load applied to the resin layer when peeling the film is different from that when there is no difference in the above-mentioned tearing force, which is appropriate. As a result, it is believed that there is also a difference in the ease of forming film marks on the resin layer. However, it is only a guess after all, and it is not limited to this.
[0054] <Effect of the Second Method>
[0055] Furthermore, according to the present invention, there can be provided a structure including a resin layer having a thickness of 50 μm or more and a small variation in thickness on a first film.
[0056] The reason why the resin layer with small thickness variation can be formed by adjusting the trouser tear force of the first film and adjusting the thickness of the first film is not necessarily clear, but it can be inferred as follows. That is, it is inferred that the surface state of the first film becomes appropriate through the above-mentioned adjustment, and even when tension is applied to the above-mentioned first film, the force can be withstood, so wrinkles are difficult to form, and as a result, the resin layer formed on the first film is easily formed, and the thickness variation of the above-mentioned resin layer can be suppressed. However, it is only a speculation after all, and it is not limited to this. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 This is a schematic cross-sectional view showing one embodiment of the structure of the present invention.
[0058] Figure 2 This is a schematic cross-sectional view showing one embodiment of the structure of the present invention. DETAILED DESCRIPTION
[0059] <Detailed description of the first method>
[0060] <Structure>
[0061] The structure of the present invention comprises a first film, a resin layer and a second film in sequence, and the first film and the second film satisfy the specific conditions described below. In the present invention, by making the first film and the second film satisfy the specific conditions described below, a structure can be provided, which is easy to distinguish the front and back sides of the multi-layer structure, and the resin layer is not easy to have film marks when the second film is peeled off.
[0062] The structure of the present invention will be described with reference to the drawings. Figure 1 Schematic cross-sectional view showing one embodiment of the structure of the present invention. Figure 1 As shown, the structure 1 includes a first film 10, a resin layer 20 provided on one surface of the first film 10, and a second film 30 provided on the surface of the resin layer 20 opposite to the surface provided with the first film 10. Hereinafter, each component constituting the structure of the present invention will be described.
[0063] [First film and second film]
[0064] In the present invention, the difference in trouser tear strength and haze between the first film and the second film, or the difference in L* value, a* value, and b* value in the Lab color space may be within the ranges described below.
[0065] The first film in the present invention has the function of supporting the resin layer of the structure, and is a film coated with a resin composition when the resin layer is formed. In the present invention, it refers to a film at least bonded to the resin layer when being laminated and integrally formed by heating, etc. in a manner that the resin layer side of the structure is connected to a base material such as a substrate, and preferably peeled off from the structure after the resin layer is cured. As the first film, for example, a film composed of thermoplastic resins such as a polyester film of polyethylene terephthalate and polyethylene naphthalate, a polyolefin film such as a polyethylene film and a polypropylene film, a polytetrafluoroethylene film, a polyimide film, a polyamide-imide film, a polystyrene film, etc. can be used. Among these, from the aspects of heat resistance, mechanical strength, operability, etc., polyester film and polyolefin film can be used. The surface of the resin layer of the first film can be subjected to demoulding or roughening treatment, and sputtering or an extremely thin copper foil and an adhesive layer can also be formed.
[0066] The thickness of the first film is not particularly limited and can be appropriately selected according to the application. In terms of mechanical strength, handleability, etc., the thickness of the first film is preferably 12 μm to 125 μm, more preferably 15 μm to 75 μm.
[0067] The second film in the present invention refers to a film arranged on the opposite side of the resin layer of the first film for the purpose of preventing dust from adhering to the surface of the resin layer of the structure and improving operability. In particular, in the present invention, it refers to a film peeled off from the structure before lamination when the resin layer side of the structure is laminated and integrally formed by heating, etc. in a manner that is in contact with a base material such as a substrate. As the second film, for example, a film composed of a thermoplastic resin exemplified in the above-mentioned first film can be used. Among these, polyester film and polyolefin film are preferred from the aspects of heat resistance, mechanical strength, operability, etc. The surface of the resin layer of the second film can be subjected to demoulding treatment.
[0068] The thickness of the second film is not particularly limited and can be appropriately selected depending on the application. In terms of mechanical strength, handleability, etc., the thickness of the second film is preferably 10 μm to 100 μm, more preferably 15 μm to 50 μm.
[0069] In the structure of the present invention, the difference between the trouser-shaped tear force of the first film and the trouser-shaped tear force of the second film (= "trouser-shaped tear force of the first film" - "trouser-shaped tear force of the second film") is -0.05N or less or +0.05N or more, preferably -0.1N or less or +0.1N or more, more preferably -0.3N or less -0.1N or more +0.1N or less +0.3N or more, and further preferably more than +0.1N or less +0.3N or less. From the aspect of being less likely to have film marks, the trouser-shaped tear force of the second film is preferably smaller than the trouser-shaped tear force of the first film.
[0070] It should be noted that, in the present invention, the trouser tear strength of the first film and the second film is a value measured under the following measurement conditions using a tensile tester (manufactured by Shimadzu Corporation, EZ-SX) in accordance with JIS K 7128-1:1998 "Plastics - Test method for tear strength of films and sheets - Part 1: Trouser tear method". However, in the present invention, with regard to the measurement direction, only the longitudinal direction (MD direction) is measured regardless of the presence or absence of anisotropy based on the direction.
[0071] (Measurement conditions)
[0072] ·Test room temperature and humidity: 23±2℃, 50±15%
[0073] ·Test piece size: 150mm×50mm
[0074] · Length of the cut in the center of the test piece: 75±1mm
[0075] Test speed: 200mm / min
[0076] Distance between test pieces: 75mm
[0077] The trouser tear strength of the first film and the second film can be adjusted to a desired range by adjusting the types of thermoplastic resins of the first film and the second film, the stretch ratio during film manufacturing, the film thickness, the film breaking strength, the surface roughness, etc.
[0078] In the structure of the present invention, the difference between the haze of the first film and the haze of the second film (= "haze of the first film" - "haze of the second film") is -5% or less or +5% or more. From the perspective of being easier to distinguish the front and back sides of the multilayer structure, it is preferably -8% or more or +8%, and more preferably -85% or more -8% or more or +8% or less than +85%. The haze of the first film and the second film can be adjusted to the desired range by adjusting the surface roughness of the first film and the second film, the addition and type of colorant, the type of thermoplastic resin, the stretch ratio during film manufacturing, the thickness of the film, etc. By making the difference in the haze of the first film and the second film meet the above conditions, it is easy to distinguish the front and back sides of the multilayer structure.
[0079] It should be noted that, in the present invention, the haze of the first film and the second film is a value measured on the film itself using a haze meter in accordance with ASTM D 1003.
[0080] Alternatively, in the structure of the present invention, the difference between the L* value, a* value, and b* value in the Lab color space measured from the first film side of the structure and the L* value, a* value, and b* value in the Lab color space measured from the second film side of the structure (= "L* value, a* value, and b* value in the Lab color space measured from the first film side of the structure" - "L* value, a* value, and b* value in the Lab color space measured from the second film side of the structure") satisfies at least one of the following conditions (i) to (iii).
[0081] (i) The difference in L* value is -0.1 or less or +0.1 or more. From the perspective of making it easier to distinguish the front and back sides of the multilayer structure, it is preferably -10 or less or +10 or more, and more preferably -30 or more and -15 or less, or +15 or more and +30 or less.
[0082] (ii) The difference in a* value is -0.1 or less or +0.1 or more. From the perspective of making it easier to distinguish the front and back sides of the multilayer structure, it is preferably -0.3 or more or +0.3 or more, and more preferably -30 or more and -0.3 or less or +0.3 or less and +30 or less.
[0083] (iii) The difference in b* value is -1 or less or +1 or more. From the perspective of making it easier to distinguish the front and back sides of the multilayer structure, it is preferably -2 or less or +2 or more, and more preferably -10 or more and -2 or more and +2 or less than +10.
[0084] The L* value, a* value, b* value in the Lab color space measured from the first film side of the structure and the L* value, a* value, b* value in the Lab color space measured from the second film side of the structure can be adjusted to the desired range by adjusting the roughness of the surface of the first film and the second film, the amount and type of the colorant, the type of thermoplastic resin, the stretching ratio during film manufacturing, the thickness of the film, etc. By making the L* value, a* value, b* value in the Lab color space measured from the first film side of the structure and the L* value, a* value, b* value in the Lab color space measured from the second film side of the structure meet the above conditions, it is easy to distinguish the front and back of the structure of the multilayer structure. Wherein, from the aspect of being easier to distinguish, it is particularly preferred that the difference recorded in (i), i.e. the difference of the L* value, meets the above conditions.
[0085] It should be noted that in the present invention, the L* value, a* value, and b* value in the Lab color space measured from the second film side of the structure and the L* value, a* value, and b* value in the Lab color space measured from the first film side of the structure are values measured using a spectrophotometer under the following measurement conditions.
[0086] (Measurement conditions)
[0087] Reflection mode
[0088] ·Mirror reflection light processing
[0089] ·Measurement diameter: SAV (3mm)
[0090] UV condition: 100% full
[0091] Field of view: 10°
[0092] ·Incident light 65°
[0093] ·Measurement method: SCE (excluding specular reflection component)
[0094] Substrate: Black backing paper (L* value: 27.3, a* value 0.7, b* value 2.0)
[0095] [Resin layer]
[0096] The resin layer is a layer located between the first film and the second film of the structure, and is preferably a curable resin layer. The curable resin layer is a dry coating obtained by drying a curable resin composition, and may be a thermosetting resin layer cured by heating, a photocurable resin layer cured by light irradiation, or a thermosetting / photocurable resin layer cured by heating and by light irradiation.
[0097] (Curable resin composition)
[0098] The curable resin composition preferably contains at least one of a thermosetting resin and a photocurable resin, and may further contain other components.
[0099] (Thermosetting resin)
[0100] When curable resin composition includes thermosetting resin, the heat resistance of cured product is improved, and the adhesion with substrate is improved in addition. As thermosetting resin, amino resins such as melamine resin, benzoguanamine resin, melamine derivatives, benzoguanamine derivatives, isocyanate compounds, blocked isocyanate compounds, cyclic carbonate compounds, epoxy compounds, oxetane compounds, episulfide resins, bismaleimide, carbodiimide resins, etc. can be used. Among these, it is preferred that there are multiple cyclic ether groups or cyclic thioether groups (hereinafter referred to as cyclic (thio) ether groups) in the molecule. Thermosetting resin can be used alone 1 kind or two or more combinations are used.
[0101] Such a thermosetting resin having a cyclic (thio)ether group in the molecule is a compound having either or both of a 3-, 4- or 5-membered cyclic ether group or a cyclic thioether group in the molecule, and examples thereof include epoxy compounds, polyfunctional oxetane compounds, episulfide resins, etc. Among these, epoxy compounds are preferred.
[0102] Examples of the epoxy compound include bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, bisphenol E epoxy resin, bisphenol M epoxy resin, bisphenol P epoxy resin, bisphenol Z epoxy resin and the like, bisphenol A novolac epoxy resin, phenol novolac epoxy resin, cresol novolac epoxy resin and the like novolac epoxy resin, biphenyl epoxy resin, biphenyl aralkyl epoxy resin, aryl alkylene epoxy resin, tetraphenyl ethane epoxy resin, naphthalene epoxy resin, anthracene epoxy resin, phenoxy epoxy resin, dicyclopentadiene epoxy resin, norbornene epoxy resin, etc. Epoxy resin, adamantane epoxy resin, fluorene epoxy resin, methacrylate glycidyl copolymer epoxy resin, cyclohexylmaleimide and methacrylate glycidyl copolymer epoxy resin, epoxy-modified polybutadiene rubber derivative, CTBN-modified epoxy resin, trimethylolpropane polyglycidyl ether, phenyl-1,3-diglycidyl ether, biphenyl-4,4'-diglycidyl ether, 1,6-hexanediol diglycidyl ether, ethylene glycol or propylene glycol diglycidyl ether, sorbitol polyglycidyl ether, tris(2,3-epoxypropyl)isocyanurate, triglycidyl tris(2-hydroxyethyl)isocyanurate, etc.
[0103] Examples of commercially available epoxy resins include jER 828, 806, 807, YX8000, YX8034, and 834 manufactured by Mitsubishi Chemical Corporation, YD-128, YDF-170, ZX-1059, and ST-3000 manufactured by Nippon Steel Chemical & Material Co., Ltd., EPICLON 830, 835, 840, 850, N-730A, and N-695 manufactured by DIC Corporation, and RE-306 manufactured by Nippon Kayaku Co., Ltd.
[0104] Examples of the polyfunctional oxetane compound include bis[(3-methyl-3-oxetanylmethoxy)methyl]ether, bis[(3-ethyl-3-oxetanylmethoxy)methyl]ether, 1,4-bis[(3-methyl-3-oxetanylmethoxy)methyl]benzene, 1,4-bis[(3-ethyl-3-oxetanylmethoxy)methyl]benzene, (3-methyl-3-oxetanyl)methyl acrylate, and (3-ethyl-3-oxetanyl)methyl acrylate. In some embodiments, the present invention relates to polyfunctional oxetanes such as (methyl-3-ethyl-oxetanyl)methyl ester, (3-methyl-3-oxetanyl)methyl methacrylate, (3-ethyl-3-oxetanyl)methyl methacrylate, oligomers or copolymers thereof; and ethers of oxetanol and resins having hydroxyl groups such as novolac resins, poly(p-hydroxystyrene), Cardo-type bisphenols, calixarene, resorcinol calixarene or silsesquioxane. In addition, copolymers of unsaturated monomers having oxetane rings and alkyl (meth)acrylates can also be cited.
[0105] Examples of the compound having a plurality of cyclic sulfide groups in the molecule include bisphenol A type episulfide resins, etc. In addition, episulfide resins obtained by replacing the oxygen atoms of epoxy groups of novolac type epoxy resins with sulfur atoms by the same synthesis method can also be used.
[0106] Examples of amino resins such as melamine derivatives and benzoguanamine derivatives include methylolmelamine compounds, methylolbenzoguanamine compounds, methylolglycoluril compounds, and methylolurea compounds.
[0107] As the isocyanate compound, a polyisocyanate compound may be mixed. As the polyisocyanate compound, aromatic polyisocyanates such as 4,4'-diphenylmethane diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, naphthalene-1,5-diisocyanate, o-xylyl diisocyanate, m-xylyl diisocyanate and 2,4-toluene dimer; aliphatic polyisocyanates such as tetramethylene diisocyanate, hexamethylene diisocyanate, methylene diisocyanate, trimethylhexamethylene diisocyanate, 4,4-methylenebis(cyclohexyl isocyanate) and isophorone diisocyanate; alicyclic polyisocyanates such as dicycloheptane triisocyanate; and adducts, biuret bodies and isocyanurate bodies of the isocyanate compounds mentioned above.
[0108] As the blocked isocyanate compound, an addition reaction product of an isocyanate compound and an isocyanate blocking agent can be used. As the isocyanate compound capable of reacting with the isocyanate blocking agent, for example, the above-mentioned polyisocyanate compounds can be cited. As the isocyanate blocking agent, for example, phenol-based blocking agents; lactam-based blocking agents; active methylene-based blocking agents; alcohol-based blocking agents; oxime-based blocking agents; thiol-based blocking agents; amide-based blocking agents; imide-based blocking agents; amine-based blocking agents; imidazole-based blocking agents; imine-based blocking agents, etc. can be cited.
[0109] (Photocurable resin (radical polymerization))
[0110] As the photocurable resin, it is particularly preferable to use a compound having one or more ethylenically unsaturated bonds in the molecule. As the compound having an ethylenically unsaturated bond, a known and commonly used photopolymerizable oligomer, photopolymerizable vinyl monomer, and the like are used.
[0111] As photopolymerizable oligomers, unsaturated polyester oligomers, (meth)acrylate oligomers, etc. can be cited. As (meth)acrylate oligomers, epoxy (meth)acrylates such as phenol novolac epoxy (meth)acrylate, cresol novolac epoxy (meth)acrylate, and bisphenol epoxy (meth)acrylate, urethane (meth)acrylate, epoxyurethane (meth)acrylate, polyester (meth)acrylate, polyether (meth)acrylate, polybutadiene modified (meth)acrylate, etc. can be cited. It should be noted that in this specification, (meth)acrylate refers to a term that collectively refers to acrylate, methacrylate, and a mixture thereof, and the same applies to other similar expressions.
[0112] Examples of the photopolymerizable vinyl monomer include known and commonly used substances, for example, styrene derivatives such as styrene, chlorostyrene, and α-methylstyrene; vinyl esters such as vinyl acetate, vinyl butyrate, or vinyl benzoate; vinyl ethers such as vinyl isobutyl ether, vinyl n-butyl ether, vinyl tert-butyl ether, vinyl n-pentyl ether, vinyl isopentyl ether, vinyl n-octadecyl ether, vinyl cyclohexyl ether, ethylene glycol monobutyl vinyl ether, and triethylene glycol monomethyl vinyl ether; acrylamide, methacrylamide, N-hydroxymethacrylamide, N-hydroxymethyl ... (Meth)acrylamides such as -hydroxymethyl methacrylamide, N-methoxymethyl acrylamide, N-ethoxymethyl acrylamide, and N-butoxymethyl acrylamide; allyl compounds such as triallyl isocyanurate, diallyl phthalate, and diallyl isophthalate; (meth)acrylic acid esters such as 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, isobornyl (meth)acrylate, phenyl (meth)acrylate, and phenoxyethyl (meth)acrylate; (meth)acrylic acid esters such as 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, isobornyl (meth)acrylate, phenyl (meth)acrylate, and phenoxyethyl (meth)acrylate; Hydroxyalkyl (meth)acrylates such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and pentaerythritol tri(meth)acrylate; alkoxyalkylene glycol mono(meth)acrylates such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate; ethylene glycol di(meth)acrylate, butanediol di(meth)acrylates, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dimethoxy acrylate, methoxy ethyl (meth)acrylate, ethoxy ethyl (meth)acrylate; Alkylene polyol poly(meth)acrylates such as pentaerythritol hexa(meth)acrylate; polyoxyalkylene glycol poly(meth)acrylates such as diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane tri(meth)acrylate; poly(meth)acrylates such as hydroxypivalic acid neopentyl glycol di(meth)acrylate; isocyanurate type poly(meth)acrylates such as tris[(meth)acryloyloxyethyl]isocyanurate, etc.
[0113] (Photocurable resin (cationic polymerization))
[0114] As the photocurable resin, alicyclic epoxy compounds and vinyl ether compounds can be preferably used. Among them, as the alicyclic epoxy compounds, 3,4,3',4'-diepoxybiscyclohexane, 2,2-bis(3,4-epoxycyclohexyl)propane, 2,2-bis(3,4-epoxycyclohexyl)-1,3-hexafluoropropane, bis(3,4-epoxycyclohexyl)methane, 1-[1,1-bis(3,4-epoxycyclohexyl)]ethylbenzene, bis(3,4-epoxycyclohexyl)adipate, 3, Alicyclic epoxy compounds having an epoxy group, such as 4-epoxycyclohexylmethyl (3,4-epoxy)cyclohexanecarboxylate, (3,4-epoxy-6-methylcyclohexyl)methyl-3',4'-epoxy-6-methylcyclohexanecarboxylate, ethylene-1,2-bis(3,4-epoxycyclohexanecarboxylate), epoxycyclohexane, 3,4-epoxycyclohexylmethyl alcohol, and 3,4-epoxycyclohexylethyltrimethoxysilane.
[0115] Examples of the vinyl ether compound include cyclic ether-type vinyl ethers (vinyl ethers having a cyclic ether group such as an oxirane ring, an oxetane ring, or an oxolane ring) such as isosorbide divinyl ether and oxanorbornene divinyl ether; aryl vinyl ethers such as phenyl vinyl ether; alkyl vinyl ethers such as n-butyl vinyl ether and octyl vinyl ether; cycloalkyl vinyl ethers such as cyclohexyl vinyl ether; polyfunctional vinyl ethers such as hydroquinone divinyl ether, 1,4-butanediol divinyl ether, cyclohexane divinyl ether, and cyclohexanedimethanol divinyl ether; and vinyl ether compounds having a substituent such as an alkyl group or an allyl group at the α-position and / or β-position.
[0116] (Alkali soluble resin)
[0117] The curable resin composition may contain an alkali-soluble resin. As the alkali-soluble resin, a carboxyl-containing resin or a phenolic resin is preferably used. Not only does it improve the adhesion to the substrate, but in particular, if a carboxyl-containing resin is used, it is more preferred from the aspect of developability. The carboxyl-containing resin may be a carboxyl-containing photosensitive resin having an ethylenically unsaturated double bond.
[0118] (1) A carboxyl group-containing photosensitive resin obtained by reacting (meth)acrylic acid with an epoxy resin and adding a dibasic acid anhydride such as phthalic anhydride, tetrahydrophthalic anhydride, or hexahydrophthalic anhydride to a hydroxyl group present in a side chain.
[0119] (2) A carboxyl group-containing photosensitive resin obtained by epoxidizing the hydroxyl groups of an epoxy resin with epichlorohydrin, reacting the resulting polyfunctional epoxy resin with (meth)acrylic acid, and adding a dibasic acid anhydride to the generated hydroxyl groups.
[0120] (3) A carboxyl-containing photosensitive resin obtained by reacting a compound having at least one alcoholic hydroxyl group and one phenolic hydroxyl group in one molecule with a monocarboxylic acid containing an unsaturated group such as (meth) acrylic acid and an epoxy compound, and reacting the alcoholic hydroxyl group of the obtained reaction product with a polyacid anhydride such as maleic anhydride, tetrahydrophthalic anhydride, trimellitic anhydride, pyromellitic anhydride, adipic acid, etc.
[0121] (4) A compound having two or more phenolic hydroxyl groups in one molecule, such as bisphenol A, bisphenol F, bisphenol S, novolac-type phenolic resin, poly(p-hydroxystyrene), condensates of naphthol and aldehydes, condensates of dihydroxynaphthalene and aldehydes, is reacted with an alkylene oxide such as ethylene oxide and propylene oxide, the resulting reaction product is reacted with a monocarboxylic acid containing an unsaturated group such as (meth)acrylic acid, and the resulting reaction product is reacted with a polyacid anhydride to obtain a carboxyl-containing photosensitive resin.
[0122] (5) A carboxyl-containing photosensitive resin obtained by reacting a compound having two or more phenolic hydroxyl groups in one molecule with a cyclic carbonate compound such as ethylene carbonate or propylene carbonate, reacting the resulting reaction product with a monocarboxylic acid containing an unsaturated group, and reacting the resulting reaction product with a polyacid anhydride.
[0123] (6) A carbamate resin containing a terminal carboxyl group obtained by reacting an acid anhydride at the end of a carbamate resin obtained by a polyaddition reaction of a diisocyanate compound such as an aliphatic diisocyanate, a branched aliphatic diisocyanate, an alicyclic diisocyanate, an aromatic diisocyanate, and a diol compound such as a polycarbonate polyol, a polyether polyol, a polyester polyol, a polyolefin polyol, an acrylic polyol, a bisphenol A-based alkylene oxide adduct diol, or a compound having a phenolic hydroxyl group and an alcoholic hydroxyl group.
[0124] (7) In the synthesis of a carboxyl-containing urethane resin based on a polyaddition reaction of a carboxyl-containing diol compound such as diisocyanate, dimethylolpropionic acid, dimethylolbutyric acid, and a diol compound, a compound having one hydroxyl group and one or more (meth)acryloyl groups in the molecule such as (meth) hydroxyalkyl acrylate is added to produce a carboxyl-containing urethane resin with terminal (meth)acryloylation.
[0125] (8) In the synthesis of a carboxyl-containing urethane resin based on a polyaddition reaction of a diisocyanate, a carboxyl-containing diol compound and a diol compound, a compound having one isocyanate group and one or more (meth)acryloyl groups in the molecule, such as an equimolar reaction product of isophorone diisocyanate and pentaerythritol triacrylate, is added to produce a carboxyl-containing urethane resin with terminal (meth)acryloyl groups.
[0126] (9) Carboxyl group-containing resins obtained by copolymerization of an unsaturated carboxylic acid such as (meth)acrylic acid with an unsaturated group-containing compound such as styrene, α-methylstyrene, a lower alkyl (meth)acrylate, or isobutylene.
[0127] (10) A carboxyl-containing photosensitive resin is prepared by reacting a dicarboxylic acid such as adipic acid, phthalic acid, or hexahydrophthalic acid with an oxetane resin, adding a dibasic acid anhydride to the generated primary hydroxyl group, and further adding a compound having one epoxy group and one or more (meth)acryloyl groups in one molecule such as glycidyl (meth)acrylate or α-methylglycidyl (meth)acrylate to the obtained carboxyl-containing polyester resin.
[0128] (11) A carboxyl group-containing photosensitive resin obtained by adding a compound having a cyclic ether group and a (meth)acryloyl group in one molecule to the carboxyl group-containing resin of (1) to (10).
[0129] Since the carboxyl group-containing resin has a plurality of carboxyl groups in the side chains of the polymer main chain, it can be developed with a dilute alkaline aqueous solution.
[0130] The acid value of the carboxyl group-containing resin is preferably in the range of 40 to 200 mgKOH / g, more preferably in the range of 45 to 120 mgKOH / g. If the acid value of the carboxyl group-containing resin is 40 mgKOH / g or more, alkali development is easy, while if it is 200 mgKOH / g or less, a normal resist pattern is easy to draw.
[0131] The weight average molecular weight of the carboxyl group-containing resin varies depending on the resin skeleton, but is generally preferably in the range of 2,000 to 150,000, and more preferably in the range of 5,000 to 100,000. When the weight average molecular weight is 2,000 or more, the non-tackiness performance, the development resistance of the coating film after exposure, and the resolution become good. On the other hand, when the weight average molecular weight is 150,000 or less, the developability is excellent.
[0132] As the carboxyl group-containing resin, other than those listed above may be used, and one kind thereof may be used alone or two or more kinds thereof may be used as a mixture.
[0133] As the phenolic resin, phenolic resins having various skeletons synthesized using compounds having a phenolic hydroxyl group, for example, a compound having a biphenyl skeleton or a phenylene skeleton or both skeletons, or a compound containing a phenolic hydroxyl group, for example, phenol, o-cresol, p-cresol, m-cresol, 2,3-xylenol, 2,4-xylenol, 2,5-xylenol, 2,6-xylenol, 3,4-xylenol, 3,5-xylenol, catechol, resorcinol, hydroquinone, methylhydroquinone, 2,6-dimethylhydroquinone, trimethylhydroquinone, pyrogallol, phloroglucinol, etc. can be used.
[0134] For example, known and commonly used phenolic resins such as phenol novolac resin, alkylphenol novolac resin, bisphenol A novolac resin, dicyclopentadiene phenolic resin, Xylok phenolic resin, terpene-modified phenolic resin, polyvinylphenol, bisphenol F, bisphenol S phenolic resin, polyparahydroxystyrene, condensates of naphthol and aldehydes, condensates of dihydroxynaphthalene and aldehydes can be used. These can be used alone or in combination of two or more.
[0135] In the present invention, as the alkali-soluble resin, any one of a carboxyl group-containing resin and a phenolic resin or a mixture thereof can be used.
[0136] It should be noted that, when using a material not containing ethylenically unsaturated groups as an alkali-soluble resin, it is preferred to use the above-mentioned photocurable resin in combination. The photocurable resin is photocured by irradiation with active energy rays and promotes the dissolution of the alkali-soluble resin in an alkaline aqueous solution. In either case, one or more photocurable resins can be used.
[0137] (Thermoplastic resin)
[0138] In order to improve the mechanical strength of the obtained cured film, the curable resin composition may further contain a thermoplastic resin. The thermoplastic resin is preferably soluble in a solvent. When soluble in a solvent, the softness of the dry film is improved, and the generation of cracks and powdering can be suppressed. As the thermoplastic resin, there can be cited thermoplastic polyhydroxy polyether resins, phenoxy resins as condensates of epichlorohydrin and various bifunctional phenolic compounds, or phenoxy resins in which the hydroxyl groups present in the hydroxy ether part of its skeleton are esterified with various acid anhydrides or acid chlorides, polyvinyl acetal resins, polyamide resins, polyamide-imide resins, block copolymers, polymer resins having a glass transition temperature of less than 20°C and a weight average molecular weight of more than 10,000, etc. As the above-mentioned polymer resin, an acrylate copolymer is preferred. The thermoplastic resin can be used alone or in combination of two or more.
[0139] (Curing agent)
[0140] The curable resin composition may contain a curing agent. Examples of the curing agent include phenolic resins, polycarboxylic acids and anhydrides thereof, cyanate resins, active ester resins, maleimide compounds, alicyclic olefin polymers, etc. The curing agent may be used alone or in combination of two or more.
[0141] The curing agent is preferably mixed in a ratio of functional groups such as epoxy groups of thermosetting resins that can undergo a thermal curing reaction and functional groups in the curing agent that react with the functional groups to a ratio of functional groups of the curing agent / functional groups that can undergo a thermal curing reaction (equivalent ratio) = 0.2 to 2. By making the functional groups of the curing agent / functional groups that can undergo a thermal curing reaction (equivalent ratio) within the above range, roughening of the film surface in the decontamination process can be prevented. More preferably, the functional groups of the curing agent / functional groups that can undergo a thermal curing reaction (equivalent ratio) = 0.2 to 1.5.
[0142] (Curing accelerator)
[0143] The curable resin layer may contain a curing accelerator, which accelerates the thermal curing reaction and is used to further improve the properties such as adhesion, chemical resistance, and heat resistance. Specific examples of such curing accelerators include: imidazole and its derivatives; guanamines such as 2,4-diamino-6-methyl-1,3,5-triazine and benzoguanamine; polyamines such as diaminodiphenylmethane, meta-phenylenediamine, meta-phenylenediamine, diaminodiphenyl sulfone, dicyandiamide, urea, urea derivatives, melamine, and polyhydrazides; organic acid salts and / or epoxy adducts thereof; amine complexes of boron trifluoride; triazine derivatives such as ethyldiamino-s-triazine, 2,4-diamino-s-triazine, and 2,4-diamino-6-xylyl-s-triazine; trimethylamine, triethanolamine, N,N-dimethyloctylamine, N-benzyldimethylamine, pyridine, N-methylmorpholine, hexa(N-methyl)melamine, 2,4,6-tris(dimethylaminophenol), tetramethylguanidine, and meta-aminophenol. Amines; polyphenols such as polyvinylphenol, polyvinylphenol bromide, phenol novolac, alkylphenol novolac; organic phosphines such as tributylphosphine, triphenylphosphine, tri-2-cyanoethylphosphine; phosphonium salts such as tri-n-butyl(2,5-dihydroxyphenyl)phosphonium bromide and hexadecyltributylphosphonium chloride; quaternary ammonium salts such as benzyltrimethylammonium chloride and phenyltributylammonium chloride; the above-mentioned polyacid anhydrides; photocationic polymerization catalysts such as diphenyliodonium tetrafluoroborate, triphenylsulfonium hexafluoroantimonate, and 2,4,6-triphenylthiopyranium hexafluorophosphate; styrene-maleic anhydride resin; equimolar reactants of phenylisocyanate and dimethylamine, equimolar reactants of organic polyisocyanates such as toluene diisocyanate and isophorone diisocyanate and dimethylamine, metal catalysts, and other known curing accelerators. Among the curing accelerators, phosphonium salts are preferred because they can obtain BHAST resistance. The curing accelerator may be used alone or in combination of two or more.
[0144] (Photoreaction initiator)
[0145] The curable resin composition may contain a photoreaction initiator. As the photoreaction initiator, any one may be used as long as it can generate free radicals, alkalis, acids, etc. by light irradiation to cure the curable resin. As the photoreaction initiator, known and commonly used compounds such as benzophenone, acetophenone, aminoacetophenone, benzoin ether, benzyl ketal, acylphosphine oxide, oxime ether, oxime ester, and titanocene can be cited. As the photoreaction initiator, it is preferred to contain one or more selected from the group consisting of oxime ester, α-aminoacetophenone, acylphosphine oxide, and titanocene.
[0146] Examples of the oxime ester photoreaction initiator include 1,2-octanedione-1-[4-(phenylthio)-2-(O-benzoyloxime)], ethyl ketone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-, 1-(O-acetyloxime), 2-(acetoxyiminomethyl)thioxanthen-9-one, etc. The oxime ester photoreaction initiator may be a compound having a plurality of oxime ester groups.
[0147] Examples of the α-aminoacetophenone-based photoreaction initiator include 2-methyl-1-[4-(methylthio)phenyl]-2-morpholino-1-propanone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone, 2-(dimethylamino)-2-[(4-methylphenyl)methyl)-1-[4-(4-morpholino)phenyl]-1-butanone, and N,N-dimethylaminoacetophenone.
[0148] Examples of the acylphosphine oxide-based photoreaction initiator include 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide.
[0149] Examples of the titanocene-based photoreaction initiator include bis(η5-2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl)titanium.
[0150] The curable resin composition may contain a photoreaction initiator, a photoinitiator aid, and a sensitizer other than the above compounds, for example, benzoin compounds, anthraquinone compounds, thioxanthone compounds, ketal compounds, xanthone compounds, and tertiary amine compounds.
[0151] (Inorganic filler)
[0152] The curable resin composition may contain an inorganic filler. The inorganic filler preferably improves the properties of the cured product such as adhesion, mechanical strength, and linear expansion coefficient. As the inorganic filler, for example, barium sulfate, barium titanate, silicon oxide powder, micronized silicon oxide, amorphous silicon dioxide, talc, clay, magnesium carbonate, calcium carbonate, aluminum oxide, aluminum hydroxide, zirconium phosphate, mica powder, and other commonly known inorganic fillers can be used. Here, the inorganic filler preferably contains at least one of barium sulfate and silicon dioxide.
[0153] The average particle size of the inorganic filler is preferably 0.1 μm to 20 μm. It should be noted that the average particle size can be obtained using a laser diffraction particle size distribution measuring device. As a measuring device using the laser diffraction method, MicrotracBEL Co., Ltd. (Nanotrac wave) and the like can be cited. Here, the average particle size refers to a concept including an average primary particle size and an average secondary particle size.
[0154] (Organic Solvent)
[0155] The curable resin composition may contain an organic solvent for composition preparation and viscosity adjustment. As the organic solvent, for example, ketones such as methyl ethyl ketone and cyclohexanone; aromatic hydrocarbons such as toluene, xylene, and tetramethylbenzene; glycol ethers such as cellosolve, methyl cellosolve, butyl cellosolve, carbitol, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether (DPM), dipropylene glycol diethyl ether, and tripropylene glycol monomethyl ether; esters such as ethyl acetate, butyl acetate, butyl lactate, cellosolve acetate, butyl cellosolve acetate, carbitol acetate, butyl carbitol acetate, propylene glycol monomethyl ether acetate, dipropylene glycol monomethyl ether acetate, and propylene carbonate; aliphatic hydrocarbons such as octane and decane; petroleum solvents such as petroleum ether, naphtha, and solvent naphtha, etc. These organic solvents may be used alone or in combination of two or more.
[0156] (Colorant)
[0157] The curable composition may contain a colorant. The colorant is not particularly limited, and known colorants such as red, blue, green, and yellow can be used, and may be any of a pigment, a dye, and a coloring agent. In particular, the colorant preferably does not contain halogen in order to reduce the environmental burden and the impact on the human body.
[0158] Red colorants include monoazo colorants, disazo colorants, azo lake colorants, benzimidazolone colorants, perylene colorants, diketopyrrolopyrrole colorants, condensed azo colorants, anthraquinone colorants, and quinacridone colorants. Specifically, the following colorants are listed with color index (CI; issued by The Society of Dyers and Colourists) numbers.
[0159] Examples of the monoazo red colorant include Pigment Red 1, 2, 3, 4, 5, 6, 8, 9, 12, 14, 15, 16, 17, 21, 22, 23, 31, 32, 112, 114, 146, 147, 151, 170, 184, 187, 188, 193, 210, 245, 253, 258, 266, 267, 268, and 269. Examples of the disazo red colorant include Pigment Red 37, 38, and 41. In addition, examples of monoazo lake red colorants include Pigment Red 48:1, 48:2, 48:3, 48:4, 49:1, 49:2, 50:1, 52:1, 52:2, 53:1, 53:2, 57:1, 58:4, 63:1, 63:2, 64:1, 68, etc. In addition, examples of benzimidazolone red colorants include Pigment Red 171, 175, 176, 185, 208, etc. In addition, examples of perylene red colorants include Solvent Red 135, 179, Pigment Red 123, 149, 166, 178, 179, 190, 194, 224, etc. In addition, examples of diketopyrrolopyrrole red colorants include Pigment Red 254, 255, 264, 270, 272, etc. In addition, examples of condensed azo red colorants include Pigment Red 220, 144, 166, 214, 220, 221, and 242. In addition, examples of anthraquinone red colorants include Pigment Red 168, 177, and 216, and Solvent Red 149, 150, 52, and 207. In addition, examples of quinacridone red colorants include Pigment Red 122, 202, 206, 207, and 209.
[0160] As blue colorants, there are phthalocyanine-based and anthraquinone-based colorants. For pigment-based colorants, compounds classified as pigments can be cited, such as Pigment Blue 15, 15:1, 15:2, 15:3, 15:4, 15:6, 16, and 60. For dye-based colorants, solvent blue 35, 63, 68, 70, 83, 87, 94, 97, 122, 136, 67, and 70 can be used. In addition to the above, metal-substituted or unsubstituted phthalocyanine compounds can also be used.
[0161] Examples of yellow colorants include monoazo colorants, disazo colorants, condensed azo colorants, benzimidazolone colorants, isoindolinone colorants, and anthraquinone colorants. For example, anthraquinone yellow colorants include solvent yellow 163, pigment yellow 24, 108, 193, 147, 199, and 202. Examples of isoindolinone yellow colorants include pigment yellow 110, 109, 139, 179, and 185. Examples of condensed azo yellow colorants include pigment yellow 93, 94, 95, 128, 155, 166, and 180. Examples of benzimidazolone yellow colorants include pigment yellow 120, 151, 154, 156, 175, and 181. Examples of the monoazo yellow colorant include Pigment Yellow 1, 2, 3, 4, 5, 6, 9, 10, 12, 61, 62, 62:1, 65, 73, 74, 75, 97, 100, 104, 105, 111, 116, 167, 168, 169, 182, and 183. Examples of the disazo yellow colorant include Pigment Yellow 12, 13, 14, 16, 17, 55, 63, 81, 83, 87, 126, 127, 152, 170, 172, 174, 176, 188, and 198.
[0162] In addition, a coloring agent such as purple, orange, brown, or black may be added. Specifically, pigment black 1, 6, 7, 8, 9, 10, 11, 12, 13, 18, 20, 25, 26, 28, 29, 30, 31, 32, pigment violet 19, 23, 29, 32, 36, 38, 42, solvent violet 13, 36, CI pigment orange 1, 5, 13, 14, 16, 17, 24, 34, 36, 38, 40, 43, 46, 49, 51, 61, 63, 64, 71, 73, pigment brown 23, 25, carbon black, and titanium oxide may be mentioned.
[0163] [use]
[0164] The structure of the present invention is preferably used for forming a cured film of a printed circuit board, more preferably for forming a permanent protective film, and particularly preferably for forming an interlayer insulating layer, a cover layer, a solder resist or a hole filling (material). In addition, the structure of the present invention can form a cured product having excellent film strength even if it is a thin film, and therefore, it can also be appropriately used to form a pattern layer in a printed circuit board that requires thin filmization, such as a package substrate (printed circuit board used in a semiconductor package). In addition, the structure of the present invention can also be appropriately used for a flexible printed circuit board.
[0165] <Detailed description of the second method>
[0166] <Structure>
[0167] The structure of the present invention comprises a first film and a resin layer, and the first film and the resin layer satisfy the specific conditions described below. In the present invention, by making the first film and the resin layer satisfy the specific conditions described below, a structure having a resin layer with small thickness variation formed on the first film can be obtained.
[0168] The structure of the present invention will be described with reference to the drawings. Figure 2 Schematic cross-sectional view showing one embodiment of the structure of the present invention. Figure 2 As shown, the structure 1 includes a first film 10 and a resin layer 20 provided on one surface of the first film 10. Hereinafter, each component constituting the structure of the present invention will be described.
[0169] [First film]
[0170] The first film has the function of supporting the resin layer of the structural body, and is a film of the resin composition when the resin layer is formed. The first film can be peeled off from the structural body as long as the resin layer is solidified. As the first film, for example, fluororesin films such as polyolefin films such as polyester films, polyethylene films and polypropylene films, polytetrafluoroethylene films, polyimide films, polyamide-imide films, polystyrene films, etc., made of thermoplastic resins, can be used. Among these, from the aspects of heat resistance, mechanical strength, operability, etc., polyester films and polyolefin films can be used. The surface of the resin layer of the first film can be subjected to demoulding or roughening treatment, and sputtering or extremely thin copper foil and adhesive layer can also be formed.
[0171] The thickness of the first film is 30 μm or more, preferably 35 μm or more and 125 μm or less. When the thickness of the first film is within the above numerical range, it is possible to suppress the generation of longitudinal wrinkles when tension is applied to the first film.
[0172] The trouser tear strength of the first film is 0.1 N or more, preferably 0.15 N or more and 2 N or less, and more preferably 0.2 N or more and 1.5 N or less. When the trouser tear strength of the first film is within the above numerical range, wrinkles are less likely to occur, and the thickness variation of the resin layer formed on the first film can be suppressed.
[0173] In addition, in this invention, the trouser tear strength of a 1st film is the value measured using the tensile tester (made by Shimadzu Corporation, EZ-SX) under the following measurement conditions based on JIS K 7128-1:1998.
[0174] (Measurement conditions)
[0175] ·Test room temperature and humidity: 23±2℃, 50±15%
[0176] ·Test piece size: 150mm×50mm
[0177] · Length of the cut in the center of the test piece: 75±1mm
[0178] Test speed: 200mm / min
[0179] Distance between test pieces: 75mm
[0180] The trouser tear force of the first film can be adjusted to a desired range by adjusting the type of raw material of the first film, the stretch ratio during film production, the film thickness, the film breaking strength, the film heat shrinkage, etc.
[0181] The first film in the structure of the present invention can be easily controlled in thickness by coating the resin layer without deviation, and from this point of view, the deviation of the thickness of the first film is preferably ±10% or less, more preferably ±5% or less.
[0182] It should be noted that the deviation of the thickness of the first film is measured as follows. That is, from the position of 1m in the MD direction of the film end of the first film, 40mm is cut in the MD direction as a measurement sample. Regarding the measurement sample, an automatic measurement film thickness meter (manufactured by Shanwen Electric Co., Ltd., TOF-J) is used to measure 25 points at 20mm intervals along the TD direction from a position 15mm away from the film end. The maximum value, minimum value and average value are calculated from the measurement results of 25 points, and the deviation of the thickness is calculated from the difference between the maximum value and the minimum value according to the following formula.
[0183] Thickness deviation (%) = (maximum value - minimum value) / average value × 100
[0184] [Resin layer]
[0185] The resin layer is a curable resin layer formed on the first film of the structure. The curable resin layer is a dried coating obtained by drying a liquid curable resin composition, and may be a thermosetting resin layer cured by heating, a photocurable resin layer cured by light irradiation, or a thermosetting photocurable resin layer cured by heating and by light irradiation.
[0186] The thickness of the resin layer is 50 μm or more, preferably 50 μm or more and 200 μm or less. When the thickness of the resin layer is within the above numerical range, a large-sized component can be sealed.
[0187] In addition, in this invention, the thickness of a resin layer is measured by the following method.
[0188] From the position of 10m in the MD direction from the end of the coating film (resin layer) of the structure, 40mm was cut in the MD direction to serve as the measurement sample. For the measurement sample, an automatic measurement film thickness meter (manufactured by Sanwen Electric Co., Ltd., TOF-J) was used to measure 25 points at 20mm intervals in the TD direction from the position of 15mm from the end of the coating film (resin layer). The average value calculated from the measurement results of the 25 points was used as the thickness of the resin layer.
[0189] (Curable resin composition)
[0190] The curable resin composition preferably contains a curable resin and a curing agent, and may further contain other components. The curable resin composition preferably contains at least one of a thermosetting resin and a photocurable resin as the curable resin.
[0191] (Thermosetting resin)
[0192] The thermosetting resin is as described in detail in the first embodiment. It should be noted that, among the epoxy compounds, bisphenol A type epoxy resin, dicyclopentadiene type epoxy resin and phenol novolac type epoxy resin are preferably used from the perspective of optimizing the breaking point strength, thermal expansion coefficient and storage modulus of the cured coating film, more preferably two or more of them are used in combination, and further preferably three of them are used in combination.
[0193] (Photocurable resin (radical polymerization))
[0194] The photocurable resin (radical polymerization) is as described specifically in the first embodiment.
[0195] (Photocurable resin (cationic polymerization))
[0196] The photocurable resin (cationic polymerization) is as described specifically in the first embodiment.
[0197] (Alkali soluble resin)
[0198] The curable resin composition may contain an alkali-soluble resin. The alkali-soluble resin is as described specifically in the first embodiment.
[0199] (Thermoplastic resin)
[0200] The curable resin composition may further contain a thermoplastic resin in order to improve the mechanical strength of the obtained cured film. The thermoplastic resin is as described in detail in the first embodiment.
[0201] (Curing agent)
[0202] The curable resin composition may contain a curing agent. The curing agent is as described specifically in the first embodiment.
[0203] (Curing accelerator)
[0204] The curable resin layer may contain a curing accelerator. The curing accelerator is as described in detail in the first embodiment.
[0205] (Photoreaction initiator)
[0206] The curable resin composition may contain a photoreaction initiator. The photoreaction initiator is as described specifically in the first embodiment.
[0207] (Inorganic filler)
[0208] The curable resin composition may contain an inorganic filler. The inorganic filler is as described in detail in the first embodiment.
[0209] (Organic Solvent)
[0210] The curable resin composition may contain an organic solvent for composition preparation and viscosity adjustment. The organic solvent is as described specifically in the first embodiment.
[0211] (Colorant)
[0212] The curable composition may contain a colorant. The colorant is as described in detail in the first embodiment.
[0213] (Second film)
[0214] The structure of the present invention may include a second film. The second film refers to a film arranged on the opposite side of the resin layer to the first film for the purpose of preventing dust and the like from adhering to the surface of the resin layer of the structure and improving operability. The second film can be peeled off from the resin layer before being attached to the substrate during use. As the second film, for example, a film composed of a thermoplastic resin exemplified in the above-mentioned first film can be used. Among these, polyester films and polyolefin films are preferred from the aspects of heat resistance, mechanical strength, operability, etc. The surface of the second film on which the resin layer is arranged can be subjected to a demolding treatment.
[0215] The thickness of the second film is not particularly limited and can be appropriately selected depending on the application. In terms of mechanical strength, handleability, etc., the thickness of the second film is preferably 10 μm to 100 μm, more preferably 15 μm to 50 μm.
[0216] [use]
[0217] The structure of the present invention can be preferably used as the sealing and protection purposes of SAW filter. In addition, in addition to the above-mentioned purposes, it is preferably used for the formation of the cured film of the printed circuit board, more preferably for the formation of the permanent protective film, and particularly preferably for the formation of the interlayer insulating layer, the cover layer, the solder resist or the hole filling (material). In addition, the structure of the present invention can form a cured product with excellent film strength even if it is a thin film, therefore, it can also be appropriately used to form a printed circuit board requiring thin filmization, such as a pattern layer in a package substrate (a printed circuit board used in a semiconductor package). In addition, the structure of the present invention can also be appropriately used for a flexible printed circuit board.
[0218] [Electrical and electronic components]
[0219] The electric and electronic component of the present invention includes the above-mentioned printed circuit board. The electric and electronic component of the present invention can be used in various conventionally known electric devices. Among them, a SAW filter is preferred.
[0220] As the substrate, for example, a printed circuit board, a LTCC (low temperature co-fired ceramic) substrate (hereinafter also referred to as a low temperature co-fired ceramic substrate), a ceramic substrate, a silicon substrate, a metal substrate, etc. can be cited. As electrical and electronic components, sensors, MEMS, SAW chips, etc. can be cited. Among them, pressure sensors, vibration sensors, SAW chips can be appropriately used, and SAW chips are particularly preferred.
[0221] When the thermosetting resin composition is dried to form a film, lamination on the substrate is preferably performed under pressure and heating using a vacuum laminator or the like. By using such a vacuum laminator, when a substrate with components mounted thereon is used, even if there are irregularities, the substrate is closely attached, so that no bubbles are mixed in, and the sealing of the electrical and electronic components is improved. The pressurization condition is preferably about 0.1 MPa to 2.0 MPa, and the heating condition is preferably 40° C. to 120° C.
[0222] The curing after applying the thermosetting resin composition can be carried out by using a hot air circulation drying furnace, an IR furnace, a hot plate, a convection oven, etc. (using a device with a heat source using a steam-based air heating method, a method of contacting the hot air convection in the dryer, and a method of blowing it to the support using a nozzle). Among them, from the aspect of curability, a hot air circulation drying furnace is preferably used. For example, after heating the first stage at 80°C to 120°C, preferably at 90°C to 110°C for 10 minutes to 60 minutes, preferably 20 minutes to 40 minutes, and then heating and curing the second stage at 180°C to 220°C, preferably at 190°C to 210°C for 30 minutes to 120 minutes, preferably 50 minutes to 70 minutes, to form a cured product. By performing a two-stage curing, the generation of bubbles during curing can be suppressed, which is preferred from this aspect. Specifically, the residual solvent component is volatilized in the first stage, thereby suppressing the generation of bubbles during formal curing. Then, curing is completed at a higher temperature in the second stage.
[0223] Example
[0224] The present invention will be described in more detail below using examples, but the present invention is not limited to the following examples. It should be noted that, below, "parts" and "%" are based on mass unless otherwise specified.
[0225] <Example of the First Embodiment>
[0226] <Preparation Example A of Curable Resin Composition>
[0227] (Mixing Example A1)
[0228] The solvents shown in Mixing Example A1 in Table 1 below were placed in a container, heated to 50°C to prevent the solvent from volatilizing, and each epoxy resin was added and fully stirred to dissolve. Thereafter, additives and fillers were added and kneaded using a three-roll mill, and then a curing agent, a curing accelerator, and other resins were added and fully stirred using a stirrer to obtain a curable resin composition.
[0229] (Mixing Example A2)
[0230] The components were mixed in the formulation shown in Mixing Example A2 in Table 1 below, and dispersed using a three-roll mill to obtain a curable resin composition.
[0231] (Mixing Example A3)
[0232] A curable resin composition was obtained in the same manner as in Mixing Example 1 except that the formulation was changed to that shown in Mixing Example A3 shown in Table 1 below.
[0233] [Table 1]
[0234]
[0235] In Table 1, the compounding amount of each component is based on mass parts.
[0236] *1: Manufactured by Mitsubishi Chemical Corporation, jER828
[0237] *2: DIC Corporation, HP-7200L
[0238] *3: EPICLON N-740 manufactured by DIC Corporation
[0239] *4: Manufactured by Mitsubishi Chemical Corporation, ST-6100
[0240] *5: DIC Corporation, HP-4032
[0241] *6: HF-4M manufactured by Meiwa Chemical Co., Ltd.
[0242] *7: Teisan Resin SG-P3, manufactured by Nagase ChemteX Co., Ltd. *8: YX6954BH30, manufactured by Mitsubishi Chemical Corporation
[0243] *9: Made by Shikoku Chemical Industry Co., Ltd., 2E4MZ
[0244] *10: Shin-Etsu Chemical Co., Ltd., KBM-403
[0245] *11: FB-7SDX manufactured by Denka Co., Ltd.
[0246] *12: Made by Admatechs Co., Ltd., SO-C2
[0247] *13: Carbon black
[0248] *14: CI Pigment Yellow 147
[0249] *15: Phthalocyanine blue, manufactured by DIC Corporation, Fastogen Blue 5380
[0250] *16: Diethylene glycol monoethyl ether acetate
[0251] *17: Cyclohexanone
[0252] [Examples A1 to 7, Comparative Examples A1 to 4]
[0253] <Manufacturing of Structure>
[0254] In order to produce the structure, the following films were prepared.
[0255] Film A: Appearance: matte, material: PET, thickness 38 μm, tensile strength in TD direction 215 MPa, tensile strength in MD direction 243 MPa
[0256] Film B: Appearance: glossy, material: PET, thickness 50 μm, tensile strength in TD direction 235 MPa, tensile strength in MD direction 185 MPa
[0257] Film C: Appearance: matte, material: PP, thickness 16 μm, tensile strength in TD direction 250 MPa, tensile strength in MD direction 120 MPa
[0258] Film D: Appearance: glossy, material: PET, thickness 38 μm, tensile strength in TD direction 260 MPa, tensile strength in MD direction 270 MPa
[0259] Film E: Appearance: glossy, material: PET, thickness 38 μm, tensile strength in TD direction 225 MPa, tensile strength in MD direction 205 MPa
[0260] Next, in each embodiment and comparative example, a three-layer structure is obtained by combining the first film described in Table 2, the resin layer (thermosetting resin layer) using the above-mentioned curable resin composition, and the second film. Specifically, the curable resin composition obtained above is applied to the first film using a rod coater in such a manner that the film thickness of the resin layer is 100 μm after drying. Next, a hot air circulation drying furnace is used to dry at 85° C. for 5 minutes to 15 minutes in such a manner that the residual solvent amount is 1.0% to 4.0%, and a resin layer is formed on the first film. Next, a roll laminator is used to adhere the second film to the dried coating surface under the conditions of a set temperature of 90° C. and a pressure of 0.15 MPa to obtain a three-layer structure.
[0261] <Determination of Trousers Tear Strength>
[0262] The prepared film was tested for trouser tearing force using a tensile tester (EZ-SX manufactured by Shimadzu Corporation) under the following conditions in accordance with JIS K 7128-1:1998 "Plastics - Test methods for tearing strength of films and sheets - Part 1: Trouser tearing method". However, with regard to the measurement direction, regardless of the presence or absence of directional anisotropy, only the longitudinal direction (MD direction) was measured. Excluding the 20 mm from the start of tearing and the 5 mm before the end of tearing, the approximate average value of the tearing strength of the remaining 50 mm was calculated. The measurement results are shown in Table 2.
[0263] (Measurement conditions)
[0264] ·Test room temperature and humidity: 23±2℃, 50±15%
[0265] · Dimensions of test piece: 150 mm × 50 mm
[0266] · Length of notch at the center of test piece: 75 ± 1 mm
[0267] · Number of samples: 5
[0268] · Test speed: 200 mm / min
[0269] · Distance between clamps of test piece: 75 mm
[0270] <Measurement of haze>
[0271] For the film prepared above, the haze was measured using a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., NDH7000II) in accordance with ASTM D 1003. The measurement results are shown in Table 2.
[0272] <Measurement of L*a*b*>
[0273] For the first film and the second film of the structure obtained above, the L*, a*, and b* values were measured using a spectrocolorimeter (CM-2600d; manufactured by Konica Minolta Inc.) under the following conditions. It should be noted that the L*, a*, and b* values of the first film were measured from the first film side of the structure. In addition, the L*, a*, and b* values of the second film were measured from the second film side of the structure. The measurement results are shown in Table 2.
[0274] (Measurement conditions)
[0275] · Number of samples: n = 3
[0276] · Reflection mode
[0277] · Specular reflection light processing
[0278] · Measurement diameter: SAV (3 mm)
[0279] · UV condition: 100% full
[0280] · Field of view: 10°
[0281] · Incident light 65°
[0282] · Measurement method: SCE (excluding specular reflection component)
[0283] · Substrate: Black backing paper (L* value: 27.3, a* value 0.7, b* value 2.0)
[0284]
[0285] <Presence or absence of film marks>
[0286] The second film side of the structure obtained above was peeled off at an angle of 180 degrees and a speed of 2 cm / sec, and the appearance of the resin layer at this time was visually confirmed. The film marks of the resin layer were evaluated according to the following criteria. The evaluation results are shown in Table 3.
[0287] (Evaluation Criteria)
[0288] ◎: The resin layer has no film marks.
[0289] ○: The resin layer has film marks which have no influence on use.
[0290] ×: The resin layer has film marks which have a great influence on use.
[0291] <Visibility of the structure's appearance>
[0292] The visibility of the appearance of the structure obtained above was visually checked from the second film side (front side) to the first film side (back side). The visibility of the appearance of the structure was evaluated according to the following criteria. The evaluation results are shown in Table 3.
[0293] (Evaluation Criteria)
[0294] ◎: It is easy to distinguish the front and back sides of the structure.
[0295] ○: The front and back sides of the structure can be distinguished.
[0296] ×: The front and back sides of the structure cannot be distinguished.
[0297]
[0298] As can be seen from Table 3, the structure of the example of the first aspect of the present application is easy to distinguish between the front and back sides, and the resin layer is less likely to have film marks when the second film is peeled off.
[0299] <Example of the Second Embodiment>
[0300] <Preparation Example B of Curable Resin Composition>
[0301] (Mixing Example B1)
[0302] The solvents shown in the mixing example B1 in the following Table 4 were placed in a container, heated to 50°C to prevent the solvent from volatilizing, and each epoxy resin was added and fully stirred to dissolve. Thereafter, additives and fillers were added and kneaded using a three-roll mill, and then a curing agent, a curing accelerator, and other resins were added and fully stirred using a stirrer to obtain a curable resin composition.
[0303] (Mixing Example B2)
[0304] The components were mixed in the formulation shown in Compounding Example B2 in Table 4 below, and dispersed using a three-roll mill to obtain a curable resin composition.
[0305] [Table 4]
[0306]
[0307] In Table 4, the amount of each component blended is based on parts by mass.
[0308] *18: Made by Mitsubishi Chemical Corporation, jER828
[0309] *19: HP-7200L manufactured by DIC Corporation
[0310] *20: EPICLON N-740 manufactured by DIC Corporation
[0311] *21: Manufactured by Mitsubishi Chemical Corporation, ST-6100
[0312] *22: DIC Corporation, HP-4032
[0313] *23: HF-4M manufactured by Meiwa Chemical Co., Ltd.
[0314] *24: Teisan Resin SG-P3 manufactured by Nagase ChemteX Co., Ltd. (solid content: 15 mass%)
[0315] *25: Made by Mitsubishi Chemical Corporation, YX6954BH30 (solid content: 30% by mass)
[0316] *26: Made by Shikoku Chemical Industry Co., Ltd., 2E4MZ
[0317] *27: Shin-Etsu Chemical Co., Ltd., KBM-403
[0318] *28: FB-7SDX manufactured by Denka Co., Ltd.
[0319] *29: Carbon black
[0320] *30: Diethylene glycol monoethyl ether acetate
[0321] *31: Cyclohexanone
[0322] [Examples B1 to 7, Comparative Examples B1 to 4]
[0323] <Manufacturing of Structure>
[0324] In order to produce the structure, the following first film was prepared.
[0325] Film A: Material: PET, thickness 50μm, release agent on one side, tensile strength in MD direction 186MPa, elongation in MD direction 130%
[0326] Film B: Material: PET, thickness 38μm, release agent on one side, tensile strength in MD direction 206MPa, elongation in MD direction 120%
[0327] Film C: Material: PI (polyimide), thickness 50 μm, tensile strength in MD direction 300 MPa, elongation in MD direction 85%
[0328] Film D: Material: PP, thickness 30μm, adhesive layer on one side, tensile strength in MD direction M80Pa, elongation in MD direction 225%
[0329] Film E: Material: PP, thickness 15 μm, tensile strength in MD direction 100 MPa, elongation in MD direction 150%
[0330] Film G: Material: PET, thickness 125 μm, tensile strength in MD direction 225 MPa, elongation in MD direction 125%
[0331] Film H: Material: PET, thickness 25 μm, tensile strength in MD direction 186 MPa, elongation in MD direction 130%
[0332] Next, in each of the Examples and Comparative Examples, a structure was obtained by combining the first film described in Table 5 and a resin layer (curable resin layer) using the above-mentioned curable resin composition. Specifically, the curable resin composition obtained above was applied to the first film to which a tension of 100 N / m was applied in the MD direction by a die coater, and then dried at 100° C. for 3.5 minutes to form a curable resin layer to obtain a structure.
[0333] <Measurement of Thickness of First Film and Its Deviation>
[0334] From the position of 1m in the MD direction of the film end of the first film prepared above, 40mm was cut in the MD direction to serve as a measurement sample. For the measurement sample, an automatic measurement film thickness meter (manufactured by Sanwen Electric Co., Ltd., TOF-J) was used to measure 25 points at 20mm intervals in the TD direction from a position 15mm away from the film end. The maximum value, minimum value and average value were calculated from the measurement results of the 25 points, and the thickness deviation was calculated from the difference between the maximum value and the minimum value according to the following formula. The calculation results are shown in Table 5.
[0335] Thickness deviation (%) = (maximum value - minimum value) / average value × 100
[0336] <Determination of Trousers Tear Strength>
[0337] The trouser tear strength of the film prepared above was measured using a tensile tester (EZ-SX, manufactured by Shimadzu Corporation) under the following conditions in accordance with JIS K 7128-1:1998. Excluding 20 mm from the start of tearing and 5 mm before the end of tearing, the approximate average value of the tear strength of the remaining 50 mm was calculated. The measurement results are shown in Table 5.
[0338] (Measurement conditions)
[0339] ·Test room temperature and humidity: 23±2℃, 50±15%
[0340] ·Test piece size: 150mm×50mm
[0341] · Length of the cut in the center of the test piece: 75±1mm
[0342] Number of samples: 5
[0343] Test speed: 200mm / min
[0344] Distance between test pieces: 75mm
[0345] <Measurement of Resin Layer Thickness and Deviation>
[0346] From the position of 10m in the MD direction of the end of the dry coating film (resin layer) of the structure obtained above, 40mm was cut in the MD direction as a measurement sample. Regarding the measurement sample, an automatic measurement film thickness meter (manufactured by Sanwen Electric Co., Ltd., TOF-J) was used to measure 25 points at 20mm intervals along the TD direction from a position 15mm away from the end of the dry coating film (resin layer). The maximum value, minimum value and average value were calculated from the measurement results of 25 points. The average value is shown in Table 5.
[0347] Furthermore, the thickness variation was calculated from the difference between the maximum value and the minimum value according to the following formula, and evaluated according to the following criteria.
[0348] Thickness deviation (%) = (maximum value - minimum value) / average value × 100
[0349] (Evaluation Criteria)
[0350] ◎: The difference between the maximum value and the minimum value at 25 points is 5% or less with respect to the average value.
[0351] ○: The difference between the maximum value and the minimum value at 25 points is more than 5% and less than 10% with respect to the average value.
[0352] ×: The difference between the maximum value and the minimum value of 25 points exceeds 10% with respect to the average value.
[0353]
[0354] As can be seen from Table 5, although the thickness of the resin layer of the structured body of the example of the second aspect of the present application is 50 μm or more, the variation in thickness is small.
[0355] Explanation of symbols
[0356] 1 Structure
[0357] 10 First Film
[0358] 20 Resin layer
[0359] 30 Second Film
Claims
1. A structure comprising a first film, a resin layer and a second film in this order, characterized in that: The difference between the trouser-shaped tearing force of the first film and the trouser-shaped tearing force of the second film is greater than +0.05N. The difference in haze between the first film and the second film is -5% or less or +5% or more, The resin layer is a curable resin layer, The first film is selected from polyester films and polyolefin films, The second film is selected from the group consisting of polyester films and polyolefin films.
2. A structure comprising a first film, a resin layer and a second film in this order, characterized in that: The difference between the trouser-shaped tearing force of the first film and the trouser-shaped tearing force of the second film is greater than +0.05N. The difference between the L* value, a* value, and b* value in the Lab color space measured from the first film side of the structure and the L* value, a* value, and b* value in the Lab color space measured from the second film side of the structure satisfies at least one of the following conditions (i) to (iii), (i) The difference in L* value is less than -0.1 or greater than +0.1; (ii) the difference in a* values is less than -0.1 or greater than +0.1; (iii) The difference in b* value is less than -1 or greater than +1, The resin layer is a curable resin layer, The first film is selected from polyester films and polyolefin films, The second film is selected from the group consisting of polyester films and polyolefin films.
Citation Information
Patent Citations
Mold release sheet for flexible substrate material, coverlay, and bonding sheet
JP2010069760A
Thermosetting type resin composition, and thermosetting type resin film
JP2015166403A
Film roll
JP2016044035A
Dry film, cured product, printed wiring board, and method for manufacturing cured product
CN110050514A
Transparent conductive film
US20160224140A1